Quadriceps Contracture in Four Cats: a Complication of Internal Fixation of Femoral Fractures - Fries, Cindy L.; Binnington, A. G.; Cockshutt, Joanne R. (Veterinary and Comparative Orthopaedics and Traumatology, 1988)
In a series of twenty-two cats with femoral fractures repaired by internal fixation, four cases of quadriceps contracture (18.2%) were observed. Each case of contracture involved a midshaft fracture with extensive soft tissue injury. Repair with intramedullary pins and cerclage wires had been performed in each case. Exuberant callus production was noted in two cases, while in another quadriceps contracture followed injury to the ischiatic nerve. Contracture was evident two weeks postoperatively. Physiotherapy proved ineffective and surgical intervention was not undertaken as all cases were weightbearing on the affected limb.
Keywords: Quadriceps contracture; Femoral fractures; Internal fixation; Complications